Fully Exploited Oxygen Redox Reaction by the Inter‐Diffused Cations in Co‐Free Li‐Rich Materials for High Performance Li‐Ion Batteries. Issue 17 (20th July 2020) - Lee, Junghwa; Dupre, Nicolas; Jeong, Mihee; Kang, ShinYoung; Avdeev, Maxim; Gong, Yue; Gu, Lin; Yoon, Won‐Sub; Kang, Byoungwoo
Abstract: To meet the growing demand for global electrical energy storage, high‐energy‐density electrode materials are required for Li‐ion batteries. To overcome the limit of the theoretical energy density in conventional electrode materials based solely on the transition metal redox reaction, the oxygen redox reaction in electrode materials has become an essential component because it can further increase the energy density by providing additional available electrons. However, the increase in the contribution of the oxygen redox reaction in a material is still limited due to the lack of understanding its controlled parameters. Here, it is first proposed that Li‐transition metals (TMs) inter‐diffusion between the phases in Li‐rich materials can be a key parameter for controlling the oxygen redox reaction in Li‐rich materials. The resulting Li‐rich materials can achieve fully exploited oxygen redox reaction and thereby can deliver the highest reversible capacity leading to the highest energy density, ≈1100 Wh kg −1 among Co‐free Li‐rich materials. The strategy of controlling Li/transition metals (TMs) inter‐diffusion between the phases in Li‐rich materials will provide feasible way for further achieving high‐energy‐density electrode materials via enhancing the oxygen redox reaction for high‐performance Li‐ion batteries. Abstract : A new key parameter for fully exploiting the oxygen redox reaction by Li/transition metals (TMs) inter‐diffusion between the two phases in Co‐free Li‐rich materials is first proposed. The resulting Li‐rich materials can achieve fully exploited oxygen redox reaction and thereby can deliver the highest reversible capacity leading to the highest energy density, ≈1100 Wh kg −1 among Co‐free Li‐rich materials.